Taguan - Balitaan, Elizabeth S.
Amidst the changing times and the increasing number of virtually liberated women, we find ourselves trapped in a system that is hard to resist and a structure that is overwhelmingly intricate to alter. And despite loud claims and protests for equality, we are left in a dark corner silenced by our own apprehensions and fears, that the system taught us ling before we can even think for ourselves. Incest is a crime, a moral violation that is largely existent in a society like ours. And although we believe that the abuser should be held responsible for his actions and have his finger point to no one else, reality has it that more often than not, blame is placed upon the mother or worse the victim herself. Incest eventuates from patriarchal oriented structures that the Philippines has practiced long before Spain established their own. This male predominance, asserting supremacy over women and children is a matter of fact that we take, no questions asked. This film will attempt to tell a story of a family locked in a structure that many refused and failed to confront. The film would tell of the context, the situations and the characters involved based on the research and interviews on incest. It would be told through the eyes of an 11-year-old boy, who later discovers the wicked nature of his father.